Identification of tyrosine kinase inhibitors that halt Plasmodium falciparum parasitemia - Kesely, Kristina (PLoS One, 2020)
Although current malaria therapies inhibit pathways encoded in the parasite’s genome, we have looked for anti-malaria drugs that can target an erythrocyte component because development of drug resistance might be suppressed if the parasite cannot mutate the drug’s target. In search for such erythrocyte targets, we noted that human erythrocytes express tyrosine kinases, whereas the Plasmodium falciparum genome encodes no obvious tyrosine kinases. We therefore screened a library of tyrosine kinase inhibitors from Eli Lilly and Co. in a search for inhibitors with possible antimalarial activity. We report that although most tyrosine kinase inhibitors exerted no effect on parasite survival, a subset of tyrosine kinase inhibitors displayed potent anti-malarial activity. Moreover, all inhibitors found to block tyrosine phosphorylation of band 3 specifically suppressed P. falciparum survival at the parasite egress stage of its intra-erythrocyte life cycle. Conversely, tyrosine kinase inhibitors that failed to block band 3 tyrosine phosphorylation but still terminated the parasitemia were observed to halt parasite proliferation at other stages of the parasite’s life cycle. Taken together these results suggest that certain erythrocyte tyrosine kinases may be important to P. falciparum maturation and that inhibitors that block these kinases may contribute to novel therapies for P. falciparum malaria.